Educational efficiency and technology skill development: a cross-income country analysis - Zehri, Chokri; Alsadan, Abdullah; Alalmaee, Hassan (Technological and Economic Development of Economy, 2025)
The relationship between educational efficiency, technology proficiency, and economic development remains a subject of debate, with existing empirical studies producing mixed results. Our study aims to clarify this association by investigating how advancements in technology skills can enhance educational outcomes and, in turn, stimulate economic growth. We employ a dynamic panel model with fixed effects, utilizing data from 2009 to 2022 that covers 23 lower-income, 23 middle-income, and 18 higher-income countries. Our findings reveal a significant positive impact of educational efficiency and technology proficiency on economic development, particularly in low-income countries, where the synergy between these factors drives accelerated growth. In higher-income countries, the influence of educational efficiency appears minimal, but the persistent benefits of technological competencies emphasize the critical role of technology in sustaining economic progress. Robustness checks affirm the strength of these results, leading to actionable policy recommendations that prioritize investments in education and technology to foster sustainable economic development across diverse income groups. First published online 05 June 2025